The Implications of Supreme Court Circular Letter No. 3 of 2023 on the Application of the Paritas Creditorium Principle in the Bankruptcy of Apartment Developers - Seto Wahyudi; Anita Afriana; Rai Mantili (Green Publisher Indonesia, 2026)
This study examines the implications of the Supreme Court Circular Letter (SEMA) No. 3 of 2023 on the application of the paritas creditorium principle in bankruptcy cases involving apartment developers in Indonesia. The regulation has created a normative tension between the universal nature of bankruptcy law under Law No. 37 of 2004 on Bankruptcy and Suspension of Debt Payment Obligation and the judicial restriction imposed by SEMA, which states that bankruptcy petitions against apartment developers do not fulfill the requirement of simple proof. Using a normative juridical methodology with descriptive-analytical specifications, this research is grounded in literature studies of primary, secondary, and tertiary legal sources, supported by case analysis and expert interviews. The findings reveal that SEMA No. 3 of 2023 substantially degrades the implementation of the paritas creditorium principle, limits creditors’ access to collective debt resolution mechanisms, and creates legal uncertainty through dualism of norms between statutory provisions and judicial circulars. As a result, creditors—particularly consumer creditors—are compelled to seek alternative legal remedies through civil litigation, including class action lawsuits accompanied by conservatoir beslag and execution mechanisms. This study contributes to the development of bankruptcy law discourse and offers practical recommendations to restore fairness, certainty, and effectiveness in resolving debt disputes involving apartment developers.